Досвід виробництва шестигранних труб для зберігання та транспортування відпрацьованого ядерного палива - Нехаєв, М.Є.; Балаханова, Т.В.; Левченко, Г.В. (Physico-technological Institute of Metals and Alloys, 2023)
At present time nuclear waste is transported and stored at NPPs in special storage facilities, which are based on a hexagonal tubes matrix made of steel with a boron content of 1.3–1.8 %. Boron steel ChS82 (04Kh14T3R1F) is the main material for the production of solid hexagonal tubes. However, the metal consumption rate from the tubing stock to the finished hexagon was more than 400 %. This is due to the large amount of borides in the steel structure, it has good strength and hardness, but a low level of ductility both at room and at elevated temperatures. Presently there is practically no production of canister-tubes in Ukraine, the main part is purchased abroad. For these reasons in the present work the final stage of production of racks for nuclear fuel storing, rolling mill dressing and grooving of domestic hexagonal tubes made of 04Kh14T3R1F steel was tested. It has been established that in the stock hot-rolled tubes the quantity, distribution and size of borides is uneven. Annealing was carried out before cold deformation of boron steel tubes to improve paste forming properties. Carrying out the recommended TU-14-3-1680 annealing at 670 °C did not lead to a visible change in the structure, the borides shape and size remained in the same range. Mechanical properties level remained unchanged. Annealing for all samples at average temperatures of 650–1000 °C slightly increased the plasticity, while the range of values turned out to be high. Investigation of the tubes properties for two ingots within the same melting operation showed that samples of tubes made from the ingot head have plastic properties significantly higher than from the ingot bottom. Therein, the strength of the samples remained practically at the same level and did not depend on the place of metal sampling. The results of the present work made it possible to successfully carry out experimental rolling of a hexagonal tube with a diameter of 257x7 mm from the 04Kh14T3R1F steel round tube with a diameter of 288x7 mm on a pipe-forming mill 400 of the Scientific and Production Association "Dneprofmash" in four-roll and two-roll passes.